2019
DOI: 10.1111/jcmm.14881
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA F11‐AS1 inhibits HBV‐related hepatocellular carcinoma progression by regulating NR1I3 via binding to microRNA‐211‐5p

Abstract: Long non-coding RNAs (lncRNAs) could regulate growth and metastasis of hepatocellular carcinoma (HCC). In this study, we aimed to investigate the mechanism of lncRNA F11-AS1 in hepatitis B virus (HBV)-related HCC. The relation of lncRNA F11-AS1 expression in HBV-related HCC tissues to prognosis was analysed in silico. Stably HBVexpressing HepG2.2.15 cells were established to explore the regulation of lncRNA F11-AS1 by HBx protein, as well as to study the effects of overexpressed lncRNA F11-AS1 on proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…F11-AS1 can inhibit HBV-related hepatocellular carcinoma progression by regulating NR1I3 via binding to microRNA-211-5p. LINC01018 has a novel tumor suppressor role in hepatocellular carcinoma by sponging miR-182-5p [ 9 , 10 ]. We also found lower expression of m 6 A-modified MIR325HG to be correlated with worse patient survival in both LGG and GBM (Fig.…”
Section: Association Of M 6 A-modified Te Lncrnas mentioning
confidence: 99%
“…F11-AS1 can inhibit HBV-related hepatocellular carcinoma progression by regulating NR1I3 via binding to microRNA-211-5p. LINC01018 has a novel tumor suppressor role in hepatocellular carcinoma by sponging miR-182-5p [ 9 , 10 ]. We also found lower expression of m 6 A-modified MIR325HG to be correlated with worse patient survival in both LGG and GBM (Fig.…”
Section: Association Of M 6 A-modified Te Lncrnas mentioning
confidence: 99%
“…lncRNA F11-AS1 was under-expressed and attenuated tumor growth and metastasis capacity via the F11-AS1/miR-3146/PTEN axis in HCC [29]. In addition, the low expression of lncRNA F11-AS1 was correlated with poor prognosis in patients with HBV-related HCC via regulation of the miR-211-5p /NR1I3 pathway [30]. A study revealed that LINC00942 acts as an oncogene that promotes cell proliferation and colony formation and inhibits cell apoptosis, subsequently elevating METTL14-mediated m6A methylation levels in breast cancer initiation and progression by LNC942-METTL14-CXCR4/CYP1B1 signaling axis [31].…”
Section: Discussionmentioning
confidence: 94%
“…In HepG2.2.15 cells that stably express hepatitis B virus (HBV), the HBx protein inhibits the expression of the lncRNA F11-AS1 and induces that of CAR mRNA [173]. The lncRNA F11-AS1 binds to miR-211-5p, weakening its ability to bind to CAR and inhibit its expression [173].…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…In HepG2.2.15 cells that stably express hepatitis B virus (HBV), the HBx protein inhibits the expression of the lncRNA F11-AS1 and induces that of CAR mRNA [173]. The lncRNA F11-AS1 binds to miR-211-5p, weakening its ability to bind to CAR and inhibit its expression [173]. Emerging evidence has demonstrated that lncRNAs can function as competing endogenous RNAs (ceRNAs) for specific miRNAs, regulating their function and downstream targets [175].…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%